Instrumental and Theoretical Framework of Urban Sustainability in Latin America - Rosales Pérez, Natalie (2025)
This article explores the convergence between the political agendas of international organizations and academic research on urban sustainability in Latin America. Using a descriptive-analytical approach, key documents are examined, including reports from UN-Habitat, the IDB, ECLAC, and ILPES, as well as representative academic articles, to identify common themes and assess the evolution of sustainability narratives. The structure of the study includes a theoretical introduction that describes the convergence between international policies and academic studies, highlighting concepts and practices in urban sustainability. The methodology details an analysis of reports and studies addressing regional sustainability agendas from the 1990s, exploring the adopted approaches: ecological, economical, social and poverty-focused, and political and urban management. The findings reveal a bidirectional relationship between political agendas and academic perspectives, highlighting trends, gaps, and patterns in urban sustainability research in Latin America. This relationship helps identify opportunities for improvement in the formulation and implementation of sustainable urban policies, supporting the continuous advancement toward more efficient urban environmental management adapted to the region’s realities. The article thus contributes to understanding how both fields influence each other and their implications for urban sustainability in the Latin American context.